Tindakan Agresivitas Pajak dipandang dari Teori Akuntansi Positif - Dian Sulistyorini Wulandari (Owner : Riset dan Jurnal Akuntansi, 2022)
Taxes are one of the state's largest sources of income. For businesses, taxes are a burden that can reduce profits. The government wants high tax revenues, but businesses want low tax revenues. Therefore, this is a tax avoidance act that seeks to minimize the amount of tax a company pays for violating or being legal. This study aims to determine how tax aggressiveness can be seen from aggressive accounting theory. The tax aggressiveness measure uses the company's ETR. This is the income tax expense divided by the profit before income tax. The sample of this survey consists of manufacturers listed on the Indonesia Stock Exchange (IDX) between 2017 and 2019. Targeted sampling was used to select the samples, and 54 companies obtained samples. The analytical method used is multiple regression analysis. The results of this study show that the Inventory Intensity does not affect tax aggressiveness. Capital Intensity, Fixed Assets Intensity, and Firm Size have a significant positive impact on tax aggressiveness.